2002
DOI: 10.1523/jneurosci.22-12-04897.2002
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine-Expanded Ataxin-7 Promotes Non-Cell-Autonomous Purkinje Cell Degeneration and Displays Proteolytic Cleavage in Ataxic Transgenic Mice

Abstract: Spinocerebellar ataxia (SCA) type 7 is an inherited neurodegenerative disorder caused by expansion of a polyglutamine tract within the ataxin-7 protein. To determine the molecular basis of polyglutamine neurotoxicity in this and other related disorders, we produced SCA7 transgenic mice that express ataxin-7 with 24 or 92 glutamines in all neurons of the CNS, except for Purkinje cells. Transgenic mice expressing ataxin-7 with 92 glutamines (92Q) developed a dramatic neurological phenotype presenting as a gait a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 38 publications
8
137
0
Order By: Relevance
“…Quantification of immunostaining results indicated that NIs formed in 20.6% of cells expressing the mutant ATXN7 protein (n = 725 cells counted, SEM ± 1.7%), but were absent in those expressing its WT counterpart (n = 676 cells counted). To further highlight the similarities between our SCA7 astrocyte model and previously reported SCA7 patient and laboratory model data (4,5,19), we observed an apparent polyQdependent increase in ATXN7 protein stability (Fig. 1B).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Quantification of immunostaining results indicated that NIs formed in 20.6% of cells expressing the mutant ATXN7 protein (n = 725 cells counted, SEM ± 1.7%), but were absent in those expressing its WT counterpart (n = 676 cells counted). To further highlight the similarities between our SCA7 astrocyte model and previously reported SCA7 patient and laboratory model data (4,5,19), we observed an apparent polyQdependent increase in ATXN7 protein stability (Fig. 1B).…”
Section: Resultssupporting
confidence: 83%
“…Cerebellar Purkinje cell (PC) degeneration is an integral step in the development and progression of SCA7 and has been observed in several independent transgenic mouse models of the disease (2-5); however, increasing evidence indicates that glial cell dysfunction contributes significantly to polyglutamine expansion disorder pathology (2,6,7). Interestingly, two distinct SCA7 mouse models exhibit non-cell-autonomous neurodegeneration (2,4). Of these, the model used by Custer et al (2) demonstrates that astrocyte-specific expression of polyQ ATXN7, via the Gfa2 promoter (8), results in PC degeneration and the onset of SCA7 symptoms.…”
mentioning
confidence: 99%
“…Proteolytic processing of ATXN7, believed to occur in the nucleus, has been observed in SCA7 and is thought to generate smaller more toxic polyQ fragments (Garden et al, 2002;Young et al, 2007;Yu et al, 2012;Yvert et al, 2001). We have previously shown that in the stable PC12 cell model used in this study, full-length ATXN7 is mainly found in the nucleus, whereas ATXN7 fragments localize and aggregate both in the nucleus and the cytoplasm .…”
Section: Discussionmentioning
confidence: 63%
“…Even more remarkably, we show that Igfbp5 down-regulation takes place through a non-cell-autonomous mechanism. Previous work supporting the importance of intercellular interactions in polyglutamine disorders has relied on the use of a truncated fragment of huntingtin or the overexpression of the mutant ATXN7 protein in cells that provide support to PCs (25)(26)(27). To date, however, this issue has not been investigated in KI models, whereby the mutant protein is expressed in the endogenous manner such that intercellular interactions and their influence on selective vulnerability can be investigated in the endogenous disease context.…”
Section: Discussion Common Transcriptional Changes Occur In Early-symmentioning
confidence: 99%